Report of the Peoples' Commission on Patent Laws for India - Planning Commission (Planning Commission, 2003)
The Report of the Peoples’ Commission on Patent Laws for India critically examines the evolution, structure, and implications of patent laws in the context of global intellectual property regimes, particularly under the TRIPS Agreement and the Doha Declaration on Public Health. It highlights the need to balance intellectual property protection with public health priorities, especially in addressing diseases such as HIV/AIDS, tuberculosis, and malaria in developing countries. The report underscores the importance of utilizing TRIPS flexibilities, including compulsory licensing, to ensure access to affordable medicines and prevent monopolistic pricing of patented products. It reviews the shortcomings of proposed amendments to Indian patent legislation, emphasizing clearer definitions of patentability, exclusion of non-innovative pharmaceutical claims, and safeguarding national interests including security and public welfare. The Commission also advocates strengthening mechanisms such as licensing of right, regulating patent terms, enabling parallel imports, and ensuring fair pricing. Additionally, it stresses the importance of parliamentary oversight in treaty-making processes and calls for reforms to align patent laws with broader developmental goals, technological advancement, and equitable access to innovations, while situating these issues within the historical legacy of colonial patent systems and global power imbalances in intellectual property governance.
National Working Group on Patent Laws and Public Interest Legal Support and Research Centre New Delhi, India
National Working Group on Patent Laws and Public Interest Legal Support and Research Centre New Delhi, India
Keywords: Patent Laws, TRIPS Agreement, Doha Declaration, Public Health, Compulsory Licensing, Intellectual Property Rights, Pharmaceutical Patents, National Security, Patentability Scope, Technology Transfer, WTO Framework, Indian Patent Policy